Ramadhan Digital Melalui Dakwah Dan Kajian Online Untuk Generasi Milenial - Raiyan, Raiyan; Mahmudi, Mahmudi; Anida, Anida; Mursyidah, Nelly; Ramadhan, Muhammad (Aceh Journal of Community Engagement (AJCE), 2025)
This community service activity aims to strengthen the role of the millennial generation in Islamic da'wah through digital approaches during the month of Ramadhan. Conducted at the Grand Mosque of Peusangan, the program targeted congregants of the evening (Isya) and Tarawih prayers, featuring brief, contextually relevant Islamic lectures delivered in-person and later disseminated via social media platforms such as YouTube, Instagram, and TikTok. The initiative focused not only on the delivery of Islamic knowledge but also on engaging youth in the production of digital da'wah content as a form of empowerment and skill development. The results show a significant increase in participation and enthusiasm among millennials, both in attending the sessions and in sharing da'wah messages across digital channels. Quantitative and qualitative evaluations indicate that over 85% of participants experienced increased religious understanding and a heightened motivation to contribute to Islamic da'wah in the digital age. Despite facing some technical challenges, this activity demonstrated strong potential in promoting a dynamic and relevant form of da'wah aligned with contemporary societal changes and rooted in local community engagement. Therefore, digital da'wah during Ramadhan proves to be an effective medium for transforming Islamic outreach into a more inclusive and adaptive platform—bridging traditional religious values with the opportunities offered by information technology.